Pengembangan Sistem Pengelolaan Rapat di Fakultas Ilmu Komputer Universitas Brawijaya Malang dengan berbasis Web - Riesma Rahman Nia; Denny Sagita Rusdianto; Edy Santoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Meeting management is a step to plan, organize, lead and control meetings that have been scheduled. Fakultas Ilmu Komputer (FILKOM) differentites the scope of the meeting into study program meetings, department meetings, faculty meetings and committee meetings. The stages of holding meetings in FILKOM are preparation, execution and accomplishment. The first stage in preparation is to determine the chairperson of the meeting. The meeting leader determines the topic, participants and schedule. Furthermore, the secretary helps determine the room for the meeting and contacts the participants. But there are obstacles because the meeting initiator has difficulty getting the schedule of participants and the secretary has difficulty choosing a meeting room because there is no meeting room schedule. The meeting management system at FILKOM was developed to address these problems. The system development uses the waterfall model with an object-oriented approach. Testing are carried out using unit testing, integration testing and validation testing. White-box testing is used in unit and integration tests. Blackbox testing is used in validation testing. The results of all tests are 100% valid.